COMMUNICATION AS ACULTURAL ACCUULTATION PROCESS FOR RURAL STUDENTS IN IMPROVING SOCIAL IN THE FIELD OF MODERN URBAN EDUCATION - Deni Setiawan (Proceeding International Seminar of Islamic Studies, 2022)
The contents of this article show that Intercultural Communication as a Means of Acculturation in improving social life in the realm of modern urban education uses interpersonal communication, such as greeting each other with fellow students or fellow educators. In the communication that occurs between fellow students and educators with different cultural backgrounds, it can be seen from the very striking cultural acculturation. Another factor, the culture brought by the ruralization with the existing urbanized society is the mutual respect among elements of society which is highly upheld. So the regional tendency has begun to fade and has begun to form a new culture but without losing the original culture. A habit that is brought is very visible as a way of communication activity between rural students and urban students. In improving social life in the realm of modern urban education uses interpersonal communication, such as greeting each other with fellow students or fellow educators. In the communication that occurs between fellow students and educators with different cultural backgrounds, it can be seen from the very striking cultural acculturation. Another factor, the culture brought by the ruralization with the existing urbanized society is the mutual respect among elements of society which is highly upheld. So the regional tendency has begun to fade and has begun to form a new culture but without losing the original culture. A habit that is brought is very visible as a way of communication activity between rural students and urban students.Keywords: Communication, Culture, Acculturation.